A new species of the genus Neolycaena de Nicéville, 1890 from Kyrgyzstan (Lepidoptera, Lycaenidae) - Korb, Stanislav K. (Zootaxa, 2017)
A new species from the genus Neolycaena de Nicéville, 1890 (N. ittohtoriti sp. n.) is described from the mountains of Kyrgyzstan near Bishkek. The new species differs from the closely related N. tengstroemi (Erschoff, 1874) and N. carbonaria (Groum-Grshimaïlo, 1890) in morphology of the female genitalia, in some features of the wing pattern and in the COI gene sequence.